BIOTIC EFFECTS OF IMPACTS AND VOLCANISM - Keller G. (My University, 2003)
The biotic effects of late Maastrichtian mantle plume volcanism on Ninetyeast Ridge and Deccan volcanism mirror those of the Cretaceous-Tertiary (KT) mass extinction and impact event. Planktonic foraminifera responded to high stress conditions with the same impoverished and small-sized species assemblages dominated by the disaster/opportunists Guembelitria cretacea, which characterize the KT mass extinction worldwide. Similar high stress late Maastrichtian assemblages have recently been documented from Madagascar, Israel and Egypt. Biotic effects of volcanism cannot be differentiated from those of impacts, though every period of intense volcanism is associated with high stress assemblages, this is not the case with every impact. The most catastrophic biotic effects occurred at the KT boundary (65.0 Ma) when intense Deccan volcanism coincided with a major impact and caused the mass extinction of all tropical and subtropical species. The Chicxulub impact, which now appears to have predated the KT boundary by about 300 kyr, coincided with intense Deccan volcanism that resulted in high biotic stress and greenhouse warming, but no major extinctions. The unequivocal connection between intense volcanism and high stress assemblages during the late Maastrichtian to early Danian, and the evidence of multiple impacts, necessitates revision of current impact and mass extinction theories.
Keywords: VOLCANISM; IMPACTS; BIOTIC EFFECTS; MAASTRICHTIAN; CRETACEOUS-TERTIARY; DSDP SITE 216; Mesozoic::Cretaceous::Upper::Maastrichtian; Мезозой::Меловая::Верхний::Маастрихтский